Factors contributing to the use of complementary and alternative medicine among female cancer survivors in selected centres, Malaysia - Saibul, Nurfaizah (2012)
Complementary and Alternative Medicine (CAM) use is prevalent among individuals with cancer to complement the conventional medicine. This cross sectional descriptive study was conducted to identify the pattern and factors associated with CAM use among female cancer survivors in selected regions of Peninsular Malaysia. This study was a hospital and breast cancer support groups centre-based. A total of 457 survivors with breast, colorectal, cervix, ovarian and stomach cancer were recruited from 8 government hospitals and 4 breast cancer support groups. A pre-tested interviewer-administered questionnaire was used to collect information on socio-demography, cancer history, CAM practices, dietary intake and physical activity of cancer survivors. The mean age of the respondents was 53 ± 10 years and more than half (53.0%) had at least secondary education. Majority of the respondents were Malays, married and currently unemployed. Most of the respondents were breast cancer patients followed by ovarian, colorectal, stomach and cervical cancer survivors. The mean age of cancer diagnosis was 49 ± 9 years and the mean years of survival was 5 ± 4 years. A high proportion (41.4%) of respondents was diagnosed with cancer stage II. About 52.1% of respondents were overweight (34.4%) and obese (17.7%) and about 66.1% of respondents had waist circumference ≥ 80 cm. The mean energy intake of respondents was lower than the RNI for Malaysian women in all age groups. The mean intake of protein, vitamin A and vitamin C were slightly higher than the RNI while, the mean intake of thiamine, riboflavin, niacin, calcium and iron were lower than the RNI. The respondents had inadequate mean number of servings for all food groups except for grains and protein groups (meat/ fish/ poultry and legumes). Majority of the respondents reported having moderate and high levels of physical activity. A total of 49.7% of the respondents reported CAM use as complementary treatment. Vitamins (46.7%) and spiritual activities (37.0%) were the most commonly used CAM therapies. Multivitamin (51.9%) is the most frequent type of vitamin used. Common reasons for CAM use were to increase the body’s ability to perform daily activities (72.7%) and enhance immune function (60.8%). CAM users obtained CAM information mainly from friends and family members (65.7%) and physicians (25.3%). About 53% of CAM users did not communicate with their physicians regarding CAM use. Ethnicity and years of education were significantly associated with CAM use. Multivariate logistic regression showed that non-Malay women were less likely to use CAM while those with more years of education were more likely to be associated with CAM use. Although no adverse effects of CAM was reported, cancer survivors should discuss their CAM use with health professionals to prevent potential adverse effects of these therapies. More in-depth studies on CAM use among cancer survivors should be conducted in order to explore the patterns of CAM use among cancer survivors in this country.